SPOTLIGHT on 100 years of coal mining in Witbank - K. W. Falconer (The Southern African Institute of Mining and Metallurgy, 1990)
The Witbank-Middelburg Branch of The South African Institute of Mining and Metallurgy celebrated 100 years of coal mining in the Witbank area with a function held at Douglas Colliery on the 5th December, 1989. Two hundred guests associated with the industry attended the occasion, at which Mr A.A. Sealey, Chairman of Rand Mines, Coal and Base Minerals Division, unveiled a plaque presented to the municipality.